Development of sandwich-type electrochemical antibody and aptamer sensors for detection of Mycobacterium tuberculosis - Mohd Azmi, Umi Zulaikha (2020)
Early diagnosis of Mycobacterium tuberculosis is very important to reduce the number of fatal cases and allow fast recovery. This can be done by using smear microscopy method; however, the interpretation of results requires skilled personnel due to tendency of the method to produce false-negative results (lack of sensitivity). Therefore, in this study, sandwich-type electrochemical immunosensor and aptasensor were compared for detection of CFP10-ESAT6 complex antigen as a biomarker of Mycobacterium tuberculosis, based on graphene/polyaniline (GP/PANI) modified screen-printed gold electrode (SPGE). GP/PANI nanocomposite was synthesized and characterized using Raman spectroscopy and Field Emission Scanning Electron Microscope (FESEM) in order to confirm the formation of nanocomposite. Then, it was dispersed in 3-aminopropyltriethoxysilane (APTES) and used as an electrode modifier. The morphology of the fabricated GP/PANI-SPGE was analyzed using FESEM and it showed a rough and porous surface while Energy Dispersive X-ray (EDX) spectroscopy has shown all the presence elements of GP/PANI on SPGE surface. Based on cyclic voltammetry (CV) characterization, the fabricated GP/PANI-SPGE has shown a large surface area compared to unmodified electrode. Capturing probes (antiCFP10-ESAT6 antibodies or aptamer) were immobilized onto the surface of GP/PANI-SPGE. Iron/gold magnetic nanoparticles (Fe3Q4/Au MNPs) conjugated with anti-CFP10-ESAT6 was used to complete the sandwich system. The Fe3Q4/Au MNPs was synthesized and characterized using Ultraviolet-Visible (UV-Vis) spectrophotometer, High Resolution-Transmission Electron Microscopy (HR-TEM) and X-ray Diffraction (XRD) before conjugating it with anti-CFP10-ESAT6. Differential pulse voltammetry (DPV) technique was used to investigate the analytical performance of both immunosensor and aptasensor with its corresponding CFP10-ESAT6 antigen. The detection time was within 2 hours. Under optimum conditions, both sensors showed comparable results with almost the same limit of detection (LOO) of 1.47 ng/ml for immunosensor and 1.52 ng/ml for aptasensor. However, aptasensor showed better specificity and reproducibility than immunosensor. The methods developed from these processes were then integrated into a portable reader, which provides a good correlation with conventional methods on detection of M. tuberculosis in sputum samples. Henceforth, the developed biosensor demonstrated potential as a practical screening tool for M. tuberculosis detection.